Agape after all [large type] - Robles, Katherine (Romance in the park, 2024)
"When Vanessa meets Tony on a camping trip in Hickory Run State Park, she's not looking for love. She's already engaged to Collin, a man who checks everything on her list: smart, handsome, and a Christian. When, against Collin's wishes, she signs up for a Biblical Greek class, Tony inspires her, and a deep friendship develops between them. As she finds her voice, she begins to yearn for a different future than the one she had planned. Are her doubts just cold feet or is she about to marry the wrong man?"--